Hes1 deficiency causes hematopoietic stem cell exhaustion. (16th March 2020) - Ma, Zhilin; Xu, Jian; Wu, Limei; Wang, Junjie; Lin, Qiqi; Chowdhury, Fabliha A.; Mazumder, Md. Habibul H.; Hu, Gangqing; Li, Xue; Du, Wei
Abstract: The transcriptional repressor Hairy Enhancer of Split 1 (HES1) plays an essential role in the development of many organs by promoting the maintenance of stem/progenitor cells, controlling the reversibility of cellular quiescence, and regulating both cell fate decisions. Deletion of Hes1 in mice results in severe defects in multiple organs and is lethal in late embryogenesis. Here we have investigated the role of HES1 in hematopoiesis using a hematopoietic lineage‐specific Hes1 knockout mouse model. We found that while Hes1 is dispensable for steady‐state hematopoiesis, Hes1 ‐deficient hematopoietic stem cells (HSCs) undergo exhaustion under replicative stress. Loss of Hes1 upregulates the expression of genes involved in PPARγ signaling and fatty acid metabolism pathways, and augments fatty acid oxidation (FAO) in Hes1 f/f Vav1Cre HSCs and progenitors. Functionally, PPARγ targeting or FAO inhibition ameliorates the repopulating defects of Hes1 f/f Vav1Cre HSCs through improving quiescence in HSCs. Lastly, transcriptome analysis reveals that disruption of Hes1 in hematopoietic lineage alters expression of genes critical to HSC function, PPARγ signaling, and fatty acid metabolism. Together, our findings identify a novel role of HES1 in regulating stress hematopoiesis and provide mechanistic insight into the function of HES1 in HSC maintenance. Abstract : While Hes1 is dispensable for steady‐state hematopoiesis, Hes1‐deficient HSCs undergo exhaustion under replicative stress. Deletion of Hes1 deregulates genes in PPARγ signaling and fatty acid oxidation (FAO), and augments FAO in Hes1 f/f Vav1Cre hematopoietic stem cells (HSCs) and progenitors. Mechanistically, HES1 plays important role in stress hematopoiesis by regulating genes in HSC function, PPARγ signaling and fatty acid metabolism pathways.